2019
DOI: 10.22270/jddt.v9i5.3285
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties and subchronic toxicity of the standardized extract of LAMIC, a phytomedicine prototype based on aqueous extracts from trunk bark of Lannea microcarpa Engl and K. Krause

Abstract: Aims: This study investigated the antioxidant activity and the 90 days subchronic toxicity of the standardized LAMIC phytomedicine prototype based on aqueous extracts from Lannea microcarpa trunk bark. Methods: Three spectrophotometric methods were used to evaluated the antioxidant activity of LAMIC which were 2,2-Diphenyl-1-picrylhydrazyl (DPPH) free radical, 2,2’-azinobis(3-ethylbenzolin-6-sulphonate) (ABTS) radical scavenging assays and ferric reducing antioxidant power (FRAP) assays. For the standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…These methods are distinct, each evaluating antioxidant activity differently, but remain com-plementary. The extract exhibited anti-free radicals with the DPPH method comparable to that of Trolox (reference product) (Belemnaba et al, 2019). The ABTS method makes it possible to evaluate the anti-free radical activity of the hydrophilic and lipophilic compounds present in an extract (Prior et al, 2005), these results had an IC 50 (µg / mL) 0.05 ± 0.04 (APR = 20).…”
Section: Antioxidant Properties (In Vitro Studies)mentioning
confidence: 88%
See 1 more Smart Citation
“…These methods are distinct, each evaluating antioxidant activity differently, but remain com-plementary. The extract exhibited anti-free radicals with the DPPH method comparable to that of Trolox (reference product) (Belemnaba et al, 2019). The ABTS method makes it possible to evaluate the anti-free radical activity of the hydrophilic and lipophilic compounds present in an extract (Prior et al, 2005), these results had an IC 50 (µg / mL) 0.05 ± 0.04 (APR = 20).…”
Section: Antioxidant Properties (In Vitro Studies)mentioning
confidence: 88%
“…Subacute toxicity for 28 days has shown LMaq to be non-toxic up to a dose of 1000 mg/kg (Nitiéma et al, 2018b). The subchronic toxicity of LAMIC, a prototype antihypertensive phytomedicine based on the aqueous decoct of the bark of the trunks of Lannea microcarpa in male and female Wistar rats is non-toxic up to a dose of 1500 mg/kg body weight given daily for 90 days (Belemnaba et al, 2019). Also, daily oral administration of the aqueous infused of the trunk bark of Lannea microcarpa did not show any toxidrome up to a dose of 3000 mg/kg for 14 days of treatment in Wistar rats (Owusu and Antwi-Adjei, 2017).…”
Section: Toxicological Datamentioning
confidence: 99%
“…Repeated oral administration of the extract during the 28-day study did not alter serum levels of liver transaminases, including alanine aminotransferase, aspartate aminotransferase and gamma-glutamyltransferase. These parameters are considered markers of liver integrity [26][27][28] . These results suggest that the FAD extract would not have hepatotoxic effects at the doses tested 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Solubility was determined by gradually adding increasing volumes. The maximum amount of substance required for this assay was 111 mg and the maximum solvent volume was 30 mL according to the European Pharmacopoeia 5th edition [21]. The mixtures were stirred vigorously with a magnetic stirrer for 1 minute and then placed in a thermostatically controlled chamber at a temperature of 25.0 ± 0.5 °C for 15 minutes.…”
Section: Solubility Testmentioning
confidence: 99%
“…Indeed, ethnobotanical studies have indicated the use of its trunk bark in the form of decoction in the treatment of hypertension in Burkina Faso [14][15][16]. Experimental studies (in vitro, ex vivo and in vivo) have demonstrated the safety and Anti-hypertensive properties of freeze-dried aqueous decoct of the bark of the plant trunk [17][18][19][20][21][22]. Also studies of physicochemical characterization, quality control and galenic formulation have allowed the development of capsule forms based on standardized extracts dosed at 250mg [23][24][25].…”
Section: Introductionmentioning
confidence: 99%